Fermentative microbiota and chemical characterization of traditional date vinegar with promising biotechnological applications - Al-Malki, Fatma A.; Al-Kharousi, Zahra S.; Guizani, Nejib; Al-Bulushi, Ismail M.; Al-Sadi, Abdullah M. (Frontiers in Sustainable Food Systems, 2023)
The indigenous microbiotaflora of traditional date vinegar is inadequately reported in the literature, yet its understanding is necessary for the industrial development of this product. Forty home-made samples (HMS) and laboratory-made samples (LMS) of date vinegar were analyzed microbiologically and chemically. E. coli, coliforms, and Enterobacteriaceae were enumerated to evaluate the hygienic quality. Acetic acid, ethanol, and methanol contents were analyzed by headspace gas chromatography. E. coli was not detected in any sample. Coliforms and Enterobacteriaceae occurred in 75 and 67% of HMS, respectively, and in 3.6% (both groups) of LMS. The LMS had better hygienic quality and supported better growth of yeasts and AAB than the HMS. Thirty-five yeasts belonged to six genera and 55 acetic acid bacteria (AAB) to five Gluconobacter species (identified by a polymerase chain reaction). The highest content of ethanol correlated with the presence of Saccharomyces cerevisiae. Gluconobacter japonicus and Gluconobacter oxydans tolerated 7.5% ethanol. Gluconobacter frateurii survived at pH 2.59. The percentage of acetic acid was less than the international recommended standard levels and ranged from 0.09 to 3.38%, and 0.03 to 3.46% in HMS, and LMS, respectively. The content of ethanol ranged from 0.14 to 2.17%, and 0.07 to 7.81% in HMS, and LMS, respectively. Methanol was less in LMS (≤ 0.06%) than in HMS (≤ 0.17%) and its level in some samples exceeded the standard levels. In conclusion, utilizing the traditional method for producing date vinegar does not assure the production of true and safe vinegar that contains the specified levels of acetic acid and ethanol. It may also contain unacceptable levels of the toxic chemical methanol. However, a high microbial diversity of yeasts and Gluconobacter spp. was identified which indicates the potential of producing a high-quality and safe product by modifying the production process possibly by using the isolated yeasts and AAB as starter cultures.